Characterization of the novel broad-spectrum lytic phage Phage_Pae01 and its antibiofilm efficacy against Pseudomonas aeruginosa - Shi, Zhixin; Hong, Xin; Li, Zexuan; Zhang, Meijuan; Zhou, Jun; Zhao, Zhe; Qiu, Shengfeng; Liu, Genyan (Frontiers in Microbiology, 2024)
Pseudomonas aeruginosa is present throughout nature and is a common opportunistic pathogen in the human body. Carbapenem antibiotics are typically utilized as a last resort in the clinical treatment of multidrug-resistant infections caused by P. aeruginosa. The increase in carbapenem-resistant P. aeruginosa poses an immense challenge for the treatment of these infections. Bacteriophages have the potential to be used as antimicrobial agents for treating antibiotic-resistant bacteria. In this study, a new virulent P. aeruginosa phage, Phage_Pae01, was isolated from hospital sewage and shown to have broad-spectrum antibacterial activity against clinical P. aeruginosa isolates (83.6%). These clinical strains included multidrug-resistant P. aeruginosa and carbapenem-resistant P. aeruginosa. Transmission electron microscopy revealed that the phage possessed an icosahedral head of approximately 80 nm and a long tail about 110 nm, indicating that it belongs to the Myoviridae family of the order Caudovirales. Biological characteristic analysis revealed that Phage_Pae01 could maintain stable activity in the temperature range of 4 °C 60 °C and pH range of 4 10. According to the in vitro lysis kinetics of the phage, Phage_Pae01 demonstrated strong antibacterial activity. The optimal multiplicity of infection was 0.01. The genome of Phage_Pae01 has a total length of 93,182 bp and contains 176 open reading frames (ORFs). The phage genome does not contain genes related to virulence or antibiotic resistance. In addition, Phage_Pae01 effectively prevented the formation of biofilms and eliminated established biofilms. When Phage_Pae01 was combined with gentamicin, it significantly disrupted established P. aeruginosa biofilms. In conclusion, in this study, we identified a novel P. aeruginosa phage and demonstrated its effective antimicrobial properties against P. aeruginosa in both the floating and biofilm states. These findings offer a promising approach for the treatment of drug-resistant bacterial infections in clinical settings.